362 Double arm study of performing bowel anastomosis after or before hipec in patients undergoing CRS+ HIPEC for advanced epithelial ovarian cancer. (13th November 2020) - Somashekar, S; Ashwin, K; Ramya, Y; Zaveri, S; Ahuja, V; Rohit Kumar, C
Abstract : Introduction: Bowel anastomosis before or after HIPEC has been an unresolved debate. We report our experience of impact of HIPEC on anastomosis performed before or after. Methods: Patients diagnosed with advanced epithelial ovarian cancer undergoing CRS+ HIPEC who had bowel resection & anastomoses performed were included in the study. Our institution has two teams, of which one performs anastomosis before and one after HIPEC. Uni-variate and multivariate analysis performed to find factors predicting bowel complications. Results: 135 of 220 patients had bowel resection & restoration as a part of CRS+ HIPEC for advanced epithelial ovarian cancer. Of 135 patients, 66 had anastomosis before HIPEC and 69 after HIPEC. Mean PCI 13.4±4.5, blood loss 850±302.9 ml, duration of surgery 9.5±2.4 hr. Overall 57.05% had bowel resections, of which large bowel was 75.8% & small bowel 24.2% & stoma rate was 6.4%. Both the group had same number of total (55.4%vs58.6%), small (15.3%vs16.5%) & large bowel resections (44.3%vs 49.5%). We had 4 (2.9%) leak overall, of which 2 were in either groups. Prior surgical score, recurrent ovarian cancers, number of anastomosis >2, duration of surgery >8.5 hrs were significant on uni-variate analysis. On multivariate analysis prior surgical score >1 was significant. Conclusions: We conclude that leak rates & complications related to small or large bowel anastamosis is same when anastamosis is done either before or after HIPEC. However, since this is not a randomized study a well-designed multi-institutional randomized study needs to be planned for stronger evidence of the same.